Glucuronopyranosyl Polyglucopyranosyl Constituent from the Fruits of Lycium chinense - Chung, Ill-Min; Hyun Kim, Seung; Sup Ahn, Young; Ahmad, Ateeque (Asian Journal of Chemistry, 2012)
One compound b-D-glucuronopyranosyl-b-D-(6®1)-glucopyranosyl-b-D-(6®1)-b-Dglucopyranosyl-(6®1)-b-D-glucopyranosyl-(6®1)-b-D-glucopyranosyl-(6®1)-b-D-glucopyranoside (1) has been isolated for the first time from the ethyl acetate extract of fruits of Lycium chinense. Their structure has been elucidated with the help of 600 MHz NMR using 1D and 2D spectral methods viz: 1H and 13C, aided by FAB MS and IR spectroscopy.